Outcomes After Multidisciplinary Management of Primary Mediastinal Germ Cell Tumors. Issue 6 (December 2021) - Caso, Raul; Jones, Gregory D.; Bains, Manjit S.; Hsu, Meier; Tan, Kay See; Feldman, Darren R.; Funt, Samuel A.; Reuter, Victor E.; Bosl, George J.; McHugh, Deaglan; Huang, James; Molena, Daniela; et al.
Abstract : Objective: We examined management strategies, overall survival (OS), and progression-free survival (PFS) among patients with PMNSGCTs undergoing resection and multidisciplinary management at a high-volume institution. Summary of Background Data: Outcomes after resection of PMNSGCTs are not well-characterized, with limited data on factors associated with survival. Methods: We reviewed patients with PMNSGCT who underwent resection between 1980 and 2019. Median follow-up was 3.4 years. Preoperative therapy (including use of bleomycin), surgical management, recurrence, and survival were examined. Factors associated with survival were analyzed using Cox regression. Results: In total, 113 patients were included [median age, 28 years (range, 16–65)]. Preoperative serum tumor markers (STMs) normalized/decreased in 74% of patients. Pathology included necrosis only (25%), teratoma +/− necrosis (20%), viable nonteratomatous germ cell tumor +/− teratoma (41%), and secondary somatic-type malignancy +/− teratoma (20%). Bleomycin chemotherapy was not associated with pulmonary complications or 90-day mortality. Patients receiving second-line chemotherapy followed by resection had significantly worse OS and PFS than patients receiving first-line chemotherapy followed by resection. On multivariable analysis, R1/R2 resection (HR, 3.92; P < 0.001) and increasing postoperative STMs (HR, 4.98; P < 0.001) were associated with shorter PFS; necrosis on pathology (HR, 0.42, P = 0.043) was associated with longer PFS. Conclusions: In patients with PMNSGCT undergoing resection, completeness of resection, postoperative pathology, and postoperative STMs were associated with PFS. Induction bleomycin was not associated with pulmonary complications or mortality in patients undergoing resection. Patients undergoing second-line chemotherapy followed by resection have a poor prognosis, with long-term survival of 22%. Abstract : Supplemental Digital Content is available in the text